Development and validation of a noncompetitive electrochemiluminescence-based immunoassay (ECLIA) for specific determination of insulin lispro (Humalog®) in human serum to support pharmacokinetic assessments. Issue 3 (4th May 2019) - Simmons, Erica; Johnson, Derrick; Delhaye, Richard; Colwell, Jamie; Clor, Emma; Santa, Paula; Bowsher, Ronald R.
ABSTRACT: Despite the importance of insulin and insulin analogs as therapeutic agents for the treatment of type I and II diabetes mellitus (DM), bioanalysis to support regulatory submissions of analogs remains a challenging endeavor. In particular, quantitation of insulin lispro by immunoanalytical methods has largely been limited to assays that display a high degree of cross-reactivity to native insulin because this analog shares extensive primary sequence homology with endogenous insulin and its efficacious circulating concentrations are low. We report herein development of the first noncompetitive electrochemiluminescence-based immunoassay (ECLIA) for specific determination of insulin lispro in serum or plasma. The new sandwich ECLIA permits accurate assessment of insulin lispro pharmacokinetics without interference from endogenous insulin. Integral to the development of this specific immunoassay was establishment of a proprietary process for affinity production of an oligoclonal monospecific guinea pig antiserum to the unique subtle structural modification in insulin lispro. We specifically optimized the ECLIA to provide reliable performance for supporting pharmacokinetic assessments in the pharmacologically relevant concentration range from 50.0 to 5, 000 pM with robust performance up to 100, 000 pM upon dilution. We concluded the new noncompetitive ECLIA represents a useful and convenient immunoassay for accurate quantitation of insulin lispro during pharmacokinetic assessments.